Pengaruh Perencanaan Pajak Dan Profitabilitas Terhadap Nilai Perusahaan Dengan Transparansi Sebagai Variabel Moderasi Pada Perusahaan Sektor Infrastruktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2018-2021 - Mutiara Dhea Puspita; Mulyadi Mulyadi; Panata Bangar Hasioan Sianipar (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
The Effect of Tax Planning and Profitability on Company Value with Transparency as a Moderation Variation in Infrastructure Companies in 2018-2021 Listed on the Indonesia Stock Exchange (IDX). This study aims to determine (1) the Effect of Tax Planning on Company Value, (2) The Effect of Profitability on Company Value, (3) The Effect of Tax Planning in moderating the relationship between company value and transparency, (4) The Effect of Profitability in moderating the relationship between company value and transparency. The population in this study is all Infrastructure companies listed on the Indonesia Stock Exchange during the 2018-2021 period, totaling 119 companies meeting the sample criteria. For sampling techniques in this study using Nonprobability Purposive Judgment Sampling. The results show: (1) Tax Planning has a positive and significant effect on company value, ( 2) Profitability has a positive and significant effect on company value, (3) Transparency weakens tax planning on company value, (4) Transparency is not able to moderate profitability on company value.